EVALUASI AKHIR GALUR HARAPAN KACANG PANJANG (Vigna sesquipedalis L. Fruwirth) POLONG UNGU - Ratna Zulfarosda; Damanhuri Damanhuri; Budi Waluyo; Kuswanto Kuswanto (Jurnal Agrotek Tropika, 2020)
A Final Evaluation Of Expected Lines Of Yardlong Bean (Vigna sesquipedalis L. Fruwirth)  With Purple Pods. Evaluation toward expected lines yardlong bean purple pod ability conducted to obtain lines which have superiority in yield, yiled components and other traits. Evaluation was done by analyzed adaptation and stability test. Research towards 6 lines was conducted at 6 different locations based on altitude (the middle land and low land), condition areas (rainfall and temperature) as well as the conditions of cultivation (with and without mulch application). Adaptation and stability test provides information related to lines response of environmental condition for recommended cultivation on specific or all types environment. The results showed superiority pod weight per hectare of BU 1 (9,18 t ha-1) followed by BU 6 (8,81 t ha-1) and BU 4 (6,88 t ha-1). Those lines were broadly adaptive for all types of environments. Lines that adaptive in spesific environment, BU 2 (8,03 t ha-1) produced optimal yield on marginal environment, while BU 5 (10,03 t ha-1) adaptive at productive environment. Based on lines description, all lines have superiority of purple pod colored and specifically BU 3 had highest anthocyanins content.